Whole genome analysis of hepatitis B virus before and during long-term therapy in chronic infected patients: Molecular characterization, impact on treatment and liver disease progression - Belaiba, Zeineb; Ayouni, Kaouther; Gdoura, Mariem; Kammoun Rebai, Wafa; Touzi, Henda; Sadraoui, Amel; Hammemi, Walid; Yacoubi, Lamia; Abdelati, Salwa; Hamzaoui, Lamine; Msaddak Azzouz, Mohamed; Chouikha, Anissa; et al. (Frontiers in Microbiology, 2022)
Hepatitis B virus (HBV) infection remains a serious public health concern worldwide despite the availability of an efficient vaccine and the major improvements in antiviral treatments. The aim of the present study is to analyze the mutational profile of the HBV whole genome in ETV non-responder chronic HBV patients, in order to investigate antiviral drug resistance, immune escape, and liver disease progression to Liver Cirrhosis (LC) or Hepatocellular Carcinoma (HCC). Blood samples were collected from five chronic hepatitis B patients. For each patient, two plasma samples were collected, before and during the treatment. Whole genome sequencing was performed using Sanger technology. Phylogenetic analysis comparing the studied sequences with reference ones was used for genotyping. The mutational profile was analyzed by comparison with the reference sequence M32138. Genotyping showed that the studied strains belong to subgenotypes D1, D7, and D8. The mutational analysis showed high genetic variability. In the RT region of the polymerase gene, 28 amino acid (aa) mutations were detected. The most significant mutations were the pattern rtL180M + rtS202G + rtM204V, which confer treatment resistance. In the S gene, 35 mutations were detected namely sP120T, sT126S, sG130R, sY134F, sS193L, sI195M, and sL216stop were previously described to lead to vaccine, immunotherapy, and/or diagnosis escape. In the C gene, 34 mutations were found. In particular, cG1764A, cC1766G/T, cT1768A, and cC1773T in the BCP; cG1896A and cG1899A in the precore region and cT12S, cE64D, cA80T, and cP130Q in the core region were associated with disease progression to LC and/or HCC. Other mutations were associated with viral replication increase including cT1753V, cG1764A/T, cC1766G/T, cT1768A, and cC1788G in the BCP as well as cG1896A and cG1899A in the precore region. In the X gene, 30 aa substitutions were detected, of which substitutions xT36D, xP46S, xA47T, xI88F, xA102V, xI127T, xK130M, xV131I, and xF132Y were previously described to lead to LC and/or HCC disease progression. In conclusion, our results show high genetic variability in the long-term treatment of chronic HBV patients causing several effects. This could contribute to guiding national efforts to optimize relevant HBV treatment management in order to achieve the global hepatitis elimination goal by 2030.